The New Legal Process: Games People Play and the Quest for Legitimate Judicial Decision Making - Ronald J. Krotoszynski Jr. (Washington University Law Quarterly, 1999)
In this Article, I will argue in favor of a new legal process jurisprudence, analogizing the legitimacy of such an approach to the process theory that undergirds the legitimacy of contemporary athletics. In Part I, the Article describes the balkanization of contemporary jurisprudence into increasingly specialized sects. Part II examines the importance of process to contemporary athletic contests and explores the relationship of process to the legitimacy of the outcomes in those contests. In Part III, the Article completes the circle by arguing that the legitimizing effect of process plainly manifested in the context of athletics, whether at the little league, collegiate, or professional levels of competition, also manifests itself in the context of judicial contests. Finally, Part IV of the Article argues for the creation of a new, process-based theory of judicial legitimacy.
Keywords: Rule of law; Legal discourse; Sports; Dispute resolution (Law); Judicial process; Jurisprudence